Cu2ZnSnSe4 thin films prepared by selenization of one-step electrochemically deposited Cu–Zn–Sn–Se precursors - Meng, Mingming; Wan, Lei; Zou, Peng; Miao, Shiding; Xu, Jinzhang (Applied surface science, 2013)
► Selenization one-step electrochemical deposition Cu–Zn–Sn–Se precursors to fabricate CZTSe thin films for the first time. ► Studied the effect of different rate of each element in electrolyte and the influence of pH. ► Prepared Cu2ZnSnSe4 that is pure and close to stoichiometric. ► Proved the structure of CZTSe is Kesterite-type. In this research a non-vacuum strategy was reported in facile preparation of kesterite-type Cu2ZnSnSe4 (CZTSe) thin films via selenization of one-step electrochemically prepared Cu–Zn–Sn–Se precursors. The Cu–Zn–Sn–Se precursor films were prepared by electrochemical deposition from electrolytes containing CuSO4, ZnSO4, SnCl4 and H2SeO3, and the substrate is a Mo coated soda-lime glass. The CZTSe thin films were obtained by annealing the electrochemically deposited films in the selenium vapors at the temperature of 550°C. The crystal phases, micro-structures, chemical compositions and optical properties of CZTSe films have been studied by powder X-ray diffraction (XRD), scanning electron microscopy (SEM), inductively coupled plasma optical emission spectrometer (ICP-OES), Raman scattering spectrum, and UV–vis absorption spectroscopic means. The results revealed that the electrolytes with Cu:Zn:Sn:Se molar ratio of 3:70:20:3 yields nearly pure phase of kesterite, and a band gap of 0.94eV was determined by spectroscopic measurements.